Operational Analysis of Forestry Transportation Using Self-loading Trucks in a Mountainous Region - Edson Lachini (Floresta e Ambiente, 2018)
ABSTRACT This research was conducted in wood harvesting and transportation areas in the mountainous region of Espírito Santo, Brazil, aiming to analyze the road transportation of forestry wood operations with self-loading trucks. The study identified and evaluated the times, average speed, mechanical availability, level of use and operating efficiency of three different designs of self-loading trucks. According to the results, there was no statistical difference between the vehicles regarding average speed. The highest mechanical availability was found in truck A (93.2%), followed by B (84.3%) and C (79.8%). The greater degree of utilization was found in truck B (91.8%), with little variation between vehicles C (90.0%) and A (89.9%). The highest operating efficiency was observed in truck A (83.9%), followed by B (77.4%) and C (71.8%). We concluded that self-loading truck A was the most efficient.